Outcomes of cardiac CT investigations in patients from the Rapid Access Chest Pain clinic with consideration to additional CT modalities and individual risk factors. (4th February 2022) - Juffry, L; Lim, F; Ahmad, S R; Johar, S
Abstract: Funding Acknowledgements: Type of funding sources: None. Coronary CT is a first line investigation according to NICE guidelines, yet there are still uncertainties in its ability to decrease adverse event rates. The high sensitivity and high negative predictive value of coronary CT only validates low to moderate pre-test probability of attaining significant CAD due to its low positive predictive value. Improving outcomes in coronary CT could avoid events and limit the use of invasive modalities such as invasive coronary angiography. Increased probability of MACE with presence of risk factors could also raise the merit of risk stratification utilization for better classification. This study provides insight into the effectiveness of CT as a first-line investigation for new onset angina referred to RACPC regardless of CAD probability and any further testing. Data differences on outcome probabilities in risk stratification utilization and different CT modalities, both coronary calcium scoring and coronary angiography, raised notion that the incremental value of these tools should not be overlooked. End-outcomes would compromise of MACE composites after a 6-month follow-up. We hypothesize that patients investigated with coronary CT as opposed to without, with presence or absence of functional testing, would grant better clinical outcomes. Data on 155 patients who registered in RACPC were identified and collected from Brunei Health Information Management Systems for a one-year period (August 2018- August 2019). Information on sociodemographic, risk factors, further diagnostic testing, CT reports and event follow-up at 6 months were extracted, subject to availability. Probability of CAD in patients were classified according to CCS and CTCA results. CAD was detected in 62 (40.0%) patients with non-obstructive or obstructive CAD in addition to low to high calcium scores. Over the 6-month follow-up period, MACE occurred in 8 patients in the CT group (6.3%) and 4 (13.8%) without CT. 126 (81.3%) patients with CT did not attain MACE (p = 0.19) and chances of getting CABG after adjustments with co- founding factors were significantly lower than without CT [HR = 2.654e-06; 95% CI = 2.204e-07-3.195e-05; p= <0.001]. A higher event probability was associated with a high CCS (41.1%) (p= <0.001) than abnormal CTCA (11.4%) (p = 0.018). MACE was also associated with multiple risk factors such as age (p= <0.001), hypertension (p = 0.001), diabetes (p= <0.001), high cholesterol(p = 0.027), and abnormal total cholesterol (0.010) and creatinine levels [serum creatinine, p= 0.017; creatinine clearance, p = 0.006]. Outcomes measured were not significantly better in those with cardiac CT however risk of coronary artery bypass graft was significantly lower. CCS is better than CTCA in event prospects but both possess promising prognostic values in healthy arteries. Multiple CAD risk factors associated with MACE were likely as a result of intense atherosclerosis, marking appeal for risk stratifications and preventive measures.